Analisis Kesesuaian Laporan Pengelolaan Zakat dengan Standar PSAK 109 di Masjid Nurul Jannah Desa Poleonro Kabupaten Bone - Nurfadillah Nurfadillah; Hasbi, Hartas (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to analyze the zakat management report at Masjid Nurul Jannah in Poleonro Village, Libureng District, Bone Regency, to determine whether it complies with the PSAK 109 standard on zakat management, and to understand how the distribution of zakat takes place. The research method used is qualitative, involving interviews, observations, and document analysis. The results show that the financial reporting in the zakat management at Masjid Nurul Jannah is still very simple and does not fully comply with PSAK 109 standards. The distribution of zakat is carried out fairly and evenly, but improvements are needed to further enhance and increase the welfare of the community in the area.